A porous ternary PtPdCu alloy with a spherical network structure for electrocatalytic methanol oxidation. Issue 86 (2nd September 2016) - Fan, Yang; Zhang, Yan; Cui, Ying; Wang, Jiaoli; Wei, Mengmeng; Zhang, Xinkang; Li, Wei
Abstract : A porous ternary alloy Pt5 PdCu5 was prepared, which exhibits a unique spherical network structure with a high specific surface area of 86.9 m 2 g −1 and enhanced electrocatalytic activity towards methanol oxidation. Abstract : A porous ternary alloy Pt5 PdCu5 was prepared via hydrothermal reaction in a water–ethylene glycol mixed solvent by using the block copolymer Pluronic P123 as a structure-directing agent. The as-prepared Pt5 PdCu5 alloy exhibits a unique spherical porous network structure with a high specific surface area of 86.9 m 2 g −1, which represented one of the highest values reported for Pt-based nanostructures. In contrast, a Pt5 PdCu5 alloy with a normal sponge-like porous network structure was obtained under the same synthetic conditions in the absence of P123. The electrochemical experiments show that the Pt5 PdCu5 with a spherical porous network possesses substantially enhanced electrocatalytic activity towards the methanol oxidation reaction (MOR) than its counterpart with a sponge-like porous network.